Incidence and impact of venous thromboembolism in hospitalized patients with acute pancreatitis - Keller, Karsten; Sivanathan, Visvakanth; Farmakis, Ioannis T.; Schmitt, Volker H.; Espinola-Klein, Christine; Schmidt, Frank P.; Münzel, Thomas; Konstantinides, Stavros; Hobohm, Lukas (Digestive and liver disease, 2024)
Background - Acute pancreatitis (AP) and venous thromboembolism (VTE) remain common and potentially lethal disease entities. AP might be an important trigger of systemic inflammtion and may activate the coagulation system with increased VTE risk. - Methods - The German nationwide inpatient sample was screened for patients admitted due to AP (ICD-code K85) 2005-2019. AP hospitalizations were stratified for VTE as well as risk-factors and the impact of VTE on in-hospital case-fatality rate were investigated. - Results - Overall, 797,364 hospitalizations of patients due to AP (aged in median 56.0 [IQR 44.0-71.0] years), 39.2% females) were detected in Germany 2005-2019. Incidence of VTE in hospitalized AP patients was 1764.8 per 100,000 hospitalizations (1.8%) with highest VTE rate between 5th and 6th decade. Cancer (OR 1.656 [95%CI 1.513-1.812], P < 0.001), any surgery (OR 4.063 [95%CI 3.854-4.284], P < 0.001), and heart failure (OR 1.723 [95%CI 1.619-1.833], P < 0.001) were independently associated with VTE occurrence. Case-fatality (8.8% vs. 2.7%, P < 0.001) was more than 3-fold higher in AP patients with than without VTE. VTE was associated with increased case-fatality in AP patients (OR 3.925 [95%CI 3.684-4.181], P < 0.001). - Conclusions - VTE is a life-threatening event in hospitalized AP patients associated with an almost 4-fold increased case-fatality rate. Cancer, any surgery, thrombophilia and heart failure were important risk factors for occurrence of VTE in AP.